Evaluating eating behavior treatments by FDA standards - Tomiyama, A. Janet; Ahlstrom, Britt; Mann, Traci (Frontiers in Psychology, 2014)
Behavioral treatments for obesity are not evaluated by the same criteria as pharmaceutical drugs, even though treatments such as low-calorie dieting are widely prescribed, require the patients’ time and investment, and may have risks. The Food and Drug Administration (FDA) has a procedure for evaluating drugs, in which drugmakers must answer the following questions: (1) Is the treatment safe? (2) How dangerous is the condition the intervention is treating? (3) Is the treatment effective? (4) Is the treatment safe and effective for large numbers of people? We argue that using this framework to evaluate behavioral interventions could help identify unanswered research questions on their efficacy and effectiveness, and we use the example of low-calorie dieting to illustrate how FDA criteria might be applied in the context of behavioral medicine.